Knowing the unknowable God : Ibn-Sina, Maimonides, Aquinas - Burrell, David B. (University of Notre Dame Press, 1986)
In Knowing the Unknowable God, David Burrell traces the intellectual intermingling of Muslim, Jewish, and Christian traditions that made possible the medieval synthesis that served as the basis for Western theology. He shows how Aquinas's study of the Muslim philosopher Ibn-Sina and the Jewish thinker Moses Maimonides affected the disciplined use of language when speaking of divinity and influenced his doctrine of God.